Cortical thickness and gyrification index measuring cognition in Parkinson's disease. (30th September 2021) - Chaudhary, Shefali; Kumaran, S. Senthil; Goyal, Vinay; Kaloiya, G. S.; Kalaivani, M.; Jagannathan, N. R.; Sagar, Rajesh; Mehta, Nalin; Srivastava, A. K.
Abstract: Objective: Cortical dynamics is driven by cortico-cortical connectivity and it characterizes cortical morphological features. These brain surface features complement volumetric changes and may offer improved understanding of disease pathophysiology. Hence, present study aims to investigate surface features; cortical thickness (CT) and gyrification index (GI) in Parkinson's disease (PD) patients of normal cognition (PD-CN), cognitively impaired patients with PD (PD-CI) in comparison with cognitively normal healthy controls (HC) to better elucidate cognition linked features in PD. Method: Anatomical MRI (3DT1) was carried out in 30 HC (56.53 ± 8.42 years), 30 PD-CN (58.8 ± 6.07 years), and 30 PD-CI (60.3 ± 6.43 years) subjects. Whole brain ROI based parcellation using Desikan-Killiany (DK-40) atlas followed by regional CT and GI differentiation [with 'age' and 'total intracranial volume' (TIV) correction], multiple linear regression (with 'age', 'TIV', and 'education' correction) with clinical variables, ROC analysis, and CT-GI correlation across the groups was used for data analysis. Results: Widespread cortical thinning with regional GI reduction was evident in PD-CI with respect to other two groups (HC and PD-CN), and with absence of such alterations in PD-CN compared to HC. Frontal, parietal, and temporal CT/GI significantly correlated with cognition and presented classification abilities for cognitive state in PD. Mean regional CT and GI were found negatively correlated across groups with heterogeneous regions. Conclusion: Fronto-parietal and temporal regions suffer cognition associated cortical thinning and GI reduction. CT may serve better discriminator properties and may be more consistent than GI in studying cognition in PD. Heterogeneous surface dynamics across the groups may signify neuro-developmental alterations in PD.